HPV16-LINC00393 Integration Alters Local 3D Genome Architecture in Cervical Cancer Cells - Xu, Xinxin; Han, Zhiqiang; Ruan, Yetian; Liu, Min; Cao, Guangxu; Li, Chao; Li, Fang (Frontiers in Cellular and Infection Microbiology, 2021)
High-risk human papillomavirus (hrHPV) infection and integration were considered as essential onset factors for the development of cervical cancer. However, the mechanism on how hrHPV integration influences the host genome structure remains not fully understood. In this study, we performed in situ high-throughput chromosome conformation capture (Hi-C) sequencing, chromatin immunoprecipitation and sequencing (ChIP-seq) and RNA-sequencing (RNA-seq) in two cervical cells, 1) NHEK normal human epidermal keratinocyte; and 2) HPV16-integrated SiHa tumorigenic cervical cancer cells. Our results reveal that the HPV-LINC00393 integrated chromosome 13 exhibited significant genomic variation and differential gene expression, which was verified by calibrated CTCF and H3K27ac ChIP-Seq chromatin restructuring. Importantly, HPV16 integration led to differential responses in topologically associated domain (TAD) boundaries, with a decrease in the tumor suppressor KLF12 expression downstream of LINC00393. Overall, this study provides significant insight into the understanding of HPV16 integration induced 3D structural changes and their contributions on tumorigenesis, which supplements the theory basis for the cervical carcinogenic mechanism of HPV16 integration.